2021
DOI: 10.48550/arxiv.2108.09874
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the power of Sobolev tests for isotropy under local rotationally symmetric alternatives

Abstract: We consider one of the most classical problems in multivariate statistics, namely the problem of testing isotropy, or equivalently, the problem of testing uniformity on the unit hypersphere S p−1 of R p . Rather than restricting to tests that can detect specific types of alternatives only, we consider the broad class of Sobolev tests. While these tests are known to allow for omnibus testing of uniformity, their non-null behavior and consistency rates, unexpectedly, remain largely unexplored. To improve on this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Essentially, this is because the local Bahadur efficiency does not make a statement about rates of consistency under which a statistic might nevertheless recognize the alternative. For example, the authors of [18] prove that the Bingham test, which has structural resemblance with T n, 2 , reliably recognizes a von Mises-Fisher distribution under certain rates of consistency. Hence, it might be interesting to explore the problem of rates of consistency, possibly even for very general alternatives like rotationally symmetric distributions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Essentially, this is because the local Bahadur efficiency does not make a statement about rates of consistency under which a statistic might nevertheless recognize the alternative. For example, the authors of [18] prove that the Bingham test, which has structural resemblance with T n, 2 , reliably recognizes a von Mises-Fisher distribution under certain rates of consistency. Hence, it might be interesting to explore the problem of rates of consistency, possibly even for very general alternatives like rotationally symmetric distributions.…”
Section: Discussionmentioning
confidence: 99%
“…Another indication for the inconsistency of T n, β can be seen in the case β = 1, which essentially concerns the Rayleigh test. The authors of [18] have shown that, in the rather general context of rotationally symmetric alternatives with a location and concentration parameter and a defining angular function, the Rayleigh test is blind against certain local alternatives. These local alternatives show polynomial decrease of the concentration parameter towards zero (hence yielding the null hypothesis) and the odd-order derivatives of their angular function vanish at zero.…”
Section: Consistencymentioning
confidence: 99%